Agroforestry alters the fluxes of greenhouse gases of Moso bamboo plantation soil. (1st November 2022) - Shi, Man; Li, Quan; Zhang, Han; Sun, Jilei; Zhang, Junbo; Song, Xinzhang
Abstract: Agroforestry systems are widely applied in China and have both economic and ecological benefits. However, relatively few prior studies have investigated the relative ecological benefits of various agroforestry systems. In the present study, the static chamber method, quantitative polymerase chain reaction, high throughput sequencing were used to establish the differences in greenhouse gases (GHGs) fluxes and explore the bacterial and fungal populations affecting GHGs fluxes under different agroforestry systems, including pure Moso bamboo forest (CK), bamboo + Bletilla striata (BB), bamboo + Dictyophora indusiata (BD), and bamboo + chickens (BC). The highest cumulative CH4 uptake and N2 O emission in spring occurred in BB while the highest cumulative CO2 emission and global warming potential (GWP) in spring occurred in BC. The Methylomirabilaceae were the key methanotrophs influencing the comparative differences in NO3 − associated CH4 uptake among the various agroforestry systems. N2 O emission was associated with pH, and nitrifiers such as the ammonia-oxidizing archaea and bacteria (Nitrospiraceae and Nitrosomonadaceae) rather than denitrifiers may be the key microbes affecting N2 O emission in different agroforestry systems. The bacteria Actinobacteriota and Fibrobacteres and the fungi Ascomycetes and Basidiomycota were the primary microbial taxa influencing CO2 emission. The lignin-decomposing Basidiomycota played more important roles in CO2 emission than the cellulose-decomposing fungi and bacteria under the various agroforestry systems. CO2 emission was positively correlated with NO3 − in the bacterial community and was negatively correlated with NO3 − in the fungal community, implying two C decomposition mechanisms caused by denitrification dominated in bacteria and those caused by microbial nitrogen mining dominated in fungi. The foregoing results suggested that bamboo + B. striata had comparatively higher ecological benefits as it is associated with low GWP and external C fixation. The present study provided valuable information for screening bamboo-based agroforestry systems with high ecological benefits. It also elucidated the microbial mechanism explaining the observed differences in GHGs fluxes between the various agroforestry systems.